Phosphorus Containing Coatings: Technologies and Applications. Issue 22 (9th June 2020) - Makha, Mohammed; Ghailane, Anas; Larhlimi, Hicham; Busch, Heinz; Alami, Jones
Abstract: Phosphorus Containing Coatings (PCCs) are an interesting class of materials that attracted considerable attention for use in different domains. A variety of PCCs characterized by outstanding electrical, biological, and chemical properties have been manufactured using various physical and chemical deposition processes. Thanks to developments in thin film and surface deposition technologies, it has become possible to manipulate the formation of PCCs according to the desired application, which has therefore been a mean of promoting this type of material towards new products and processes. This review explores the potential of the PCCs and deposition methods which can be used for their fabrication. Highlights on the connections between processing methods and the resulting film characteristics will be provided. The resulting coatings' properties are discussed in the context of the characteristics necessary for achieving high‐performance PCCs in different sectors. Important prospects for PCCs research and their practical use in different fields will also be provided, and light will be shed on the future research directions for further progress of promising PCCs for the next film technology generations. Abstract : This review gives a general overview of the opportunities offered by phosphorus containing coatings, their synthesis using different methods based on physical and chemical processes, as well as their use in various fields such as energy, electronics, biomedical, flame retardant and anticorrosion applications. At the end of the review, we highlight the future prospects and the development of this family of materials.